Comparative Hepatoprotective Efficacy of Livfit and Livomyn Against Carbon Tetrachloride Induced Hepatic Damage in Rats - MASTAN, S.K.; KUMAR, K.E.; SREEKANTH, N.; PILLAI, D.S. (Asian Journal of Chemistry, 2010)
Livfit and livomyn are polyherbal hepatoprotective formulations used in Indian system of medicine. Livfit and livomyn were evaluated for their hepatoprotective efficacy against carbon tetrachloride induced hepatic injury in rats. Biochemical parameters like total bilirubin, serum glutamic oxaloacetic transaminases (SGOT), serum glutamic pyruvate transaminases (SGPT) and alkaline phosphatase (ALP) and total proteins were estimated to assess liver function. Silymarin used as reference standard also exhibited hepatoprotective activity against carbon tetrachloride. The biochemical observations were supplemented with histopathological examination of rat liver sections. It was concluded from the study that livfit has shown more significant hepatoprotective activity against carbon tetrachloride induced hepatic damage in rats.